1989
DOI: 10.1128/mcb.9.11.5022-5033.1989
|View full text |Cite
|
Sign up to set email alerts
|

A New Myocyte-Specific Enhancer-Binding Factor That Recognizes a Conserved Element Associated with Multiple Muscle-Specific Genes

Abstract: Exposure of skeletal myoblasts to growth factor-deficient medium results in transcriptional activation of muscle-specific genes, including the muscle creatine kinase gene (mck). Tissue specificity, developmental regulation, and high-level expression of mck are conferred primarily by a muscle-specific enhancer located between base pairs (bp) -1350 and -1048 relative to the transcription initiation site (E. A. Sternberg, G. Spizz, W. M. Perry, D. Vizard, T. Weil, and E. N. Olson, Mol. Cell. Biol. 8:2896-2909, 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 62 publications
2
26
0
Order By: Relevance
“…MyHC is expressed only in terminally differentiated myotubes. 47 We observed that most cells fused into myotubes (MyHC-positive cells) expressing MEF2, confirming that transduction of primary myoblasts with lentiviral vectors encoding the CDK4 and hTERT proteins can efficiently immortalize cells without affecting their myogenicity ( Figure 1 B).
Figure 1 Primary human myoblasts are efficiently immortalized after transduction with lentiviruses encoding for CDK4 and hTERT (A) Primary myoblast cells were transduced with lentiviral vectors encoding the CDK4 and hTERT proteins.
…”
Section: Resultssupporting
confidence: 67%
“…MyHC is expressed only in terminally differentiated myotubes. 47 We observed that most cells fused into myotubes (MyHC-positive cells) expressing MEF2, confirming that transduction of primary myoblasts with lentiviral vectors encoding the CDK4 and hTERT proteins can efficiently immortalize cells without affecting their myogenicity ( Figure 1 B).
Figure 1 Primary human myoblasts are efficiently immortalized after transduction with lentiviruses encoding for CDK4 and hTERT (A) Primary myoblast cells were transduced with lentiviral vectors encoding the CDK4 and hTERT proteins.
…”
Section: Resultssupporting
confidence: 67%
“…By using the two alternative alleles for each variant, a total of 213 differential putative TF-binding sites (TFBS) (out of which 82 were unique) were observed ( Table S7, Supplementary Materials ); out of which 41 (14 being unique) relative, overall, to ten TFs with known literature evidence supporting their involvement in muscle metabolism and/or muscle development, i.e., COMP1 (cooperates with myogenic proteins 1, 2), C/EBP (CCAAT/enhancer binding protein, 12), MYOG (Myogenin, 2), COUP (Chicken Ovalbumin Upstream Promoter-transcription factor II, 2), MEF2 (Myocyte Enhancer Factor-2, 16), SRF (Serum Response Factor, 1), DELTAEF1 (Zinc Finger E-Box Binding Homeobox 1, 1), PBX1 (PBX Homeobox 1, 3), MYOD (Myoblast Determination Protein 1, 1) and E2F (Retinoblastoma-Binding Protein, 1). Out of them, MEF2, DELTAEF1 and MYOG are involved in promoting and regulating the skeletal muscle cell differentiation program during myogenesis [ 41 , 42 , 43 ]. Moreover, MYOG and MYOD belong to a family of proteins known as myogenic regulatory factor (MRF) that plays a major role in regulating the skeletal muscle differentiation [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Not only the spacing but also the content of cis -regulatory elements have been shown to have a dramatic effect on biological processes (such as development) in eukaryotes . While enhancer elements alone can lack discernible activity, in concert with other elements they typically evoke robust expression patterns upon associated genes . Recent efforts have been dedicated to identifying mammalian enhancer elements, where naturally occurring sequences were assessed in parallel to identify the essential elements of transcriptional networks. , …”
Section: Resultsmentioning
confidence: 99%
“…101 While enhancer elements alone can lack discernible activity, in concert with other elements they typically evoke robust expression patterns upon associated genes. 102 Recent efforts have been dedicated to identifying mammalian enhancer elements, where naturally occurring sequences were assessed in parallel to identify the essential elements of transcriptional networks. 103,104 Although much work has been done to characterize the behavior and identity of naturally occurring enhancers, and to develop synthetic tools to control mammalian gene expression, issues persist in the implementation of such components toward broader applications.…”
Section: ■ Results and Discussionmentioning
confidence: 99%